The Pink Pills of Dr. Williams: what an anemia medication can tell us about racism and sexism? - Léo Neto, Nivaldo Aureliano; Fernandes, Kelly Meneses (Khronos, 2024)
The history of drug development can be understood from different nuances and perspectives, with undeniable links between the pharmaceutical industry, economics and scientific development. This article analyzes the ads for the drug Dr. Williams Pink Pills, announced in a Journal of Ceará state in the beginning of the 20th century. The analysis provides us with evidence of the processes by which racist and sexist representations that discriminated against aspects of beauty and morality were fundamental aspects in determining the medication's clientele.